Logic and Language as Instruments of Scientific Thinking - Nissa Media Utami; Ulayya Dhiya Ulhaq (Gunung Djati Conference Series, 2026)
Logic and language are the two primary tools that enable humans to engage in scientific thinking. In scientific activities, both serve not only as aids to understand phenomena but also play a crucial role in organizing the reasoning process to be more structured and ensuring that ideas are conveyed clearly. Without their synergy, the reasoning process becomes prone to fallacies, and the outcomes of thought become difficult to verify. This study aims to explain the crucial roles of logic and language as instruments in the process of scientific thinking, as well as to analyze how both support the formation of rational and accountable knowledge. This research employs a qualitative approach with a descriptive method. Data collection techniques were conducted through library research. This approach was selected because the research focus is conceptual-philosophical in nature, requiring in-depth interpretation of texts and a synthesis of expert thought. The results indicate that logic functions as a regulator of consistency and validity in reasoning according to established rules, while language serves as the medium for the systematic transmission of thought. The two complement each other: logic ensures that the thinking process is free from rational defects, while language ensures that such knowledge can be understood and tested publicly. Furthermore, the discussion emphasizes that scientific language possesses three primary characteristics: informative, reproductive, and antiseptic. These three aspects guarantee objectivity and clarity in scientific communication. Mastery of logic and language is a fundamental foundation of scientific thinking. They are not merely technical means but epistemological pillars that shape how humans understand reality and produce knowledge responsibly.